2016
DOI: 10.21566/tarbitderg.279721
|View full text |Cite
|
Sign up to set email alerts
|

Orta Anadolu Sulu Koşullarında Bazı Kışlık Ekmeklik Buğday Genotiplerinin Verim ve Kalite Performanslarının Belirlenmesi

Abstract: 2009-2010, 2010-2011, 2011-2012, 2012-2013 growing season under irrigated conditions in Konya location. Grain yield, thousand grain weight, protein content, dry gluten, Zeleny sedimentation, hardness, alveograph, mixograph, bread volume and bread weight were investigated. Average values in the experiment; yield 522 kg / ha, thousand grain weight 34.9 g, protein content 13.1%, dry gluten rate 11.1%, Zeleny sedimentation 39.4 ml, hardness (PSI) 47.1, alveograph energy value 243.05 kjoul * 10, alveograph P/L rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…Important quality factors in wheat and flour standards are hectoliter weight, thousand kernel weight, color, ash content, protein content, gluten content, and sodium dodecyl sulphate (SDS) sedimentation value. The physical and physicochemical characteristics (such as density, hectoliter weight, kernel size, thousand kernel weight, color, gluten index, Zeleny and modified Zeleny sedimentation values), the chemical properties (such as moisture, protein, gluten) have been studied extensively in Triticum aestivum (Khatkar et al, 2002;Gül et al, 2012;Karaman et al, 2012;Dizlek et al, 2013a, b;Kaplan-Evlice et al, 2016;Şahin et al, 2016;Aydoğan and Soylu, 2017;Gül et al, 2020;Şahin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Important quality factors in wheat and flour standards are hectoliter weight, thousand kernel weight, color, ash content, protein content, gluten content, and sodium dodecyl sulphate (SDS) sedimentation value. The physical and physicochemical characteristics (such as density, hectoliter weight, kernel size, thousand kernel weight, color, gluten index, Zeleny and modified Zeleny sedimentation values), the chemical properties (such as moisture, protein, gluten) have been studied extensively in Triticum aestivum (Khatkar et al, 2002;Gül et al, 2012;Karaman et al, 2012;Dizlek et al, 2013a, b;Kaplan-Evlice et al, 2016;Şahin et al, 2016;Aydoğan and Soylu, 2017;Gül et al, 2020;Şahin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The sedimentation value was measured as 26.2 ml in the irrigated treatments and as 25.4 ml in the rainfed treatments. İlgün and Soylu (2019) reported that Zeleny sedimentation values ranged between 21.5-34.7 ml in a study they carried out with bread wheat genotypes in irrigated conditions under ecological conditions of Çumra and Altınekin counties in Konya province. Zeleny sedimentation is considered an indicator of protein quality and high values are desired in bread wheat (Şahin et al, 2017;Aydogan and Soylu, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Kalite ve verim özellikleri bakımından yüksek performansa sahip çeşitlerin geliştirilmesinde incelenen karakterlerin genetik yapılarının iyi bilinmesi gerekmektedir. Kuru ve sulu koşullarda ekmeklik buğday yetiştiriciliği ile ilgili yapılan araştırmalarda verim ve kalite özellikleri üzerine çevresel koşulların etkisinin farklılık gösterdiği saptanmıştır [5]. Tosun ve diğerleri [6], sulu koşullarda buğday genotiplerini geliştirmek amacıyla sulu şartlar için direkt seleksiyon veya kuru koşullarda indirekt seleksiyon ile istenen karakterlerin seçilmesi gerektiğini belirtmişlerdir.…”
Section: Introductionunclassified
“…Ayrıca, bitki boyu çeşitlerin genetik yapısı ve çevre faktörlerine bağlı olarak düşük ve orta kalıtıma sahip olduğu için kuru ve sulu koşullar için seleksiyonda önemli bir karakterdir[6,12,13]. Bulgularımız Aydoğan'ın[14], Konya'da kuru koşullarda bitki boyunun 79.50 ile 115 cm, sulu koşullarda 102 ile 133.50 cm ve Tunca'nın[15], Eskişehir kuru koşullarında 77 5. 128.8 cm ve sulu koşullarda 90-128 cm arasında değiştiğini bildiren sonuçlarından farklı bulunmuştur.…”
unclassified